2015
DOI: 10.3389/fonc.2015.00167
|View full text |Cite
|
Sign up to set email alerts
|

ROS accumulation by PEITC selectively kills ovarian cancer cells via UPR-mediated apoptosis

Abstract: Unfolded protein response (UPR) is crucial for both survival and death of mammalian cells, which is regulated by reactive oxygen species (ROS) and nutrient depletion. In this study, we demonstrated the effect of ROS-accumulation, induced by β-phenethyl isothiocyanate (PEITC), on UPR-mediated apoptosis in ovarian cancer cells. We used ovarian cancer cell lines, PA-1 and SKOV-3, with different p53 status (wild- and null-type, respectively). PEITC caused increased ROS-accumulation and inhibited proliferation sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 49 publications
(65 reference statements)
2
41
0
Order By: Relevance
“…Previous studies have elucidated possible molecular mechanisms, including apoptosis induction and proliferation inhibition. 31,32 In the current study, we verified that PEITC inhibited the migration and invasion of EOC in vitro and in vivo. We also explored the possible mechanisms of PEITC in EOC cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have elucidated possible molecular mechanisms, including apoptosis induction and proliferation inhibition. 31,32 In the current study, we verified that PEITC inhibited the migration and invasion of EOC in vitro and in vivo. We also explored the possible mechanisms of PEITC in EOC cell lines.…”
Section: Discussionmentioning
confidence: 74%
“…Recent research has shown that in contrast to the tumor-promoting ability of higher ROS levels, this biochemical property of cancer cells may have therapeutic benefits. Targeting mitochondria to increase the ROS level above a toxic threshold by exogenous ROS-generating phytochemicals to selectively kill cancer cells has been shown to be feasible in various in vitro and in vivo experimental models [29][30][31][32][33] . In the present study, TBMS1 increased ROS generation, modulated Bax and Bcl-2 expression, dissipated mitochondrial membrane potential and ultimately induced apoptosis in DU145 cells by inducing DNA fragmentation and caspase-3 cleavage in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research suggests that cancer cells exhibit high oxidative stress compared with normal cells, which plays an important role in cancer cell survival, proliferation, disruption of cell death signaling, metastasis, angiogenesis, and drug resistance [29][30][31] . Recent research has shown that in contrast to the tumor-promoting ability of higher ROS levels, this biochemical property of cancer cells may have therapeutic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…By use of [ 14 C]‐PEITC and mass spectrometry, PEITC has been found to bind HSP70, which is a component of the HSP90 multi‐chaperone complex 61. Third, PEITC has been reported to induce the UPR62 and inhibit the 20S and 26S proteasomal subunits,63 where both of these conditions have been shown to induce the HSF1‐mediated HSR.…”
Section: Peitc Activates the Hsf1‐dependent Heat Shock Responsementioning
confidence: 99%